Update on Wilms tumor - Klaudia Kister; Jakub Laskowski; Paulina Bronst; Magdalena Mazur; Aleksandra Małolepsza; Monika Zach-Źródlak; Julia Czechowska; Lidia Rosa; Natalia Rektor; Anna Szabrańska (Kazimierz Wielki University, 2023)
Background: Wilms' tumor is the most common childhood renal neoplasm. Among the worst prognosis forms are the bilateral form. The symptom complex is non-specific for malignancy; the first symptoms may include hypertension. Hematuria occurs in 30% of patients. The incidence of distant metastases at the time of diagnosis in children with Wilms' tumor is estimated to be about 20%.The purpose of this article is to present a review of the literature on the standardization of diagnosis, the latest treatment standards and to assess the prognosis of Wilms' Tumor. Matherial and methods:  Using PubMed, SCOPUS and Web of Science databases, the authors reviewed the peer-reviewed international literature from 1980-2023 using the keywords: "Wilms tumor," "renal tumor," "nephroblastoma."  Discussion: Bilateral tumors have the worst prognosis - according to the National Wilms Tumor Study Group, long-term survival is achieved in only 12% to 56% of patients. The prognosis of Wilms' tumor is also dependent on the occurrence of recurrences - local as well as localized outside the renal tissue. A factor directly affecting long-term survival is recurrence, mainly observed within 24 months after the end of therapy. The limitations of conventional therapies, including surgery, chemotherapy and radiotherapy, in preventing recurrence in WT patients and their potential to cause long-term side effects. Conclusions: Bilateral Wilms tumor is associated with more aggressive therapy than unilateral disease.In single kidney disease, therapeutic management is aimed at radical removal of all tumor foci, whereas in bilateral tumor, the goal of any management should additionally be to try to preserve the best possible renal function. Screening in children is important in cancer. General physicians should refer patients for additional imaging studies when there are any diagnostic doubts, as cancer is characterized by a long, asymptomatic development.